Educational Value in Merantau Culture of Indonesian Minangkabau Ethnic. - Ismira Ismira; Ahman Ahman; Mamat Supriatna (Universitas Ahmad Dahlan, 2018)
The present study was aimed at discovering the educational values of Minangkabau Ethnic's merantau culture to be used as educational content, particularly in Career Guidance and Counseling. The educational values were dug from various